The Role of Procurement and Supply of Agricultural Products in the Market Economy of the Country - Orujova Adjar Azhdar kyzy (International Journal on Economics, Finance and Sustainable Development, 2021)
Ensuring food security of the state is one of the most important issues in modern conditions. Effective state regulation of the agricultural sector, which is considered one of the most important and priority sectors of the economy, is considered one of the market relations in modern times, as in different periods. The agricultural sector is also the basis of food security. Preventive measures taken by the state envisage the establishment of food independence in the Republic of Azerbaijan. The "Strategic Roadmap for the National Economy", adopted on December 26, 2016, envisages a plan for the sustainable development of the agricultural sector. The establishment of the Procurement and Supply OJSC under the Ministry of Agriculture on December 14, 2018 was established to ensure that the product is collected, supplied and exported to the internal and external markets without losses